Răspuns:
[tex]x^{3} - \frac{1}{x^{3} } = 36[/tex]
Explicație pas cu pas:
[tex]x - \frac{1}{x} = 3[/tex]
Ridicăm la pătrat ambii membri:
[tex](x - \frac{1}{x} )^{2} = 9[/tex]
[tex]x^{2} - 2x*\frac{1}{x} + \frac{1}{x^{2} } = 9[/tex]
[tex]x^{2} + \frac{1}{x^{2} } = 11[/tex]
Înmulțim ambii membri cu [tex]x - \frac{1}{x}[/tex] (despre care știm că este egal cu 3)
[tex](x^{2} + \frac{1}{x^{2} } )(x-\frac{1}{x} ) = 33[/tex]
[tex]x^{3} - x + \frac{1}{x} - \frac{1}{x^{3} } = 33[/tex]
[tex]x^{3} - \frac{1}{x^{3} } = 33 + x - \frac{1}{x}[/tex]
[tex]x^{3} - \frac{1}{x^{3} } = 36[/tex]